Floracion in vitro de citrus latifolia tan - Daquinta, M.A.=700 1 Rodriguez, R.; Acosta, J.F.; Gonzalez, J.; Borroto, C.G.; Lima, H.
(En, Es)
Ilus., 15 ref.
Keywords: CITRUS LATIFOLIA; CULTIVO IN VITRO; FLORACION; CUBA